Connecting island regions: A qualitative approach to the European experience - Konstantinos Rigas (SPOUDAI - Journal of Economics and Business, 2012)
Island regions are generally dependent on transport services in order to retain cohesion with the mainland and for their socioeconomic development. Europe with its geography presents a number of island areas, with distinct characteristics, and transport needs. This paper focuses on the connectivity issue of these areas and attempts to address a number of questions concerning levels of service. By examining the general characteristics as well as the transport situation of these regions, the main factors affecting service levels are highlighted and possible general as well as specific policy options are considered.
Keywords: R48; R58; R41; O18; L92; L93; 330; regional development; cohesion policy; regional transportation; aviation; ferries; island regions